The impact of international accounting standards (IAS / IFRS) on the activation of management control tools in the governance framework to improve the performance of economic enterprises. - talal, zeghba; arioua, mohad (Journal of Research in Finance and Accounting, 2020)
This paper discusses the impact of the International Accounting Standards (IAS) on the outputs of the financial accounting system and its products, i.e. the financial statements which are the standard basis for accounting and financial information. These are considered as inputs to the management control system with its various tools of measurement and evaluation of the enterprise’s performance, so as to improve it and achieving its objectives, and maintaining its continuity